Law, pliability and the multicultural city: Documenting planning law in action. Issue 1 (27th April 2017) - Hubbard, Phil; Prior, Jason
Abstract : In this paper we focus on the deployment of certain techniques that are central to municipal law's attempt to impose order on the city, namely, development control, zoning, and change of use regulation. Drawing on the notion of inter‐legality, we argue that such practices can never be consistent or universal, and instead need to be sufficiently pliable to recognise the diversity of legal norms, assumptions and practices evident in a multicultural city. We demonstrate this with reference to the resolution of urban land‐use conflict in Sydney (Australia) showing how planning decisions have need to demonstrate flexibility within the law to achieve outcomes that are sensitive to local contingency and informed by notions of spatial justice. In conclusion we suggest that attempts to make municipal law more consistent or unified are problematic given situated discretion is required to produce cities more open to difference and diversity.